Analysis of erosivity indices with special reference to Kerala - GEETHA V; Prabhadevi P. S; Sudheer Narayanan; Er. Rema K. P (Guide) (Tavanur 1997 Department of Land and Water Resources and Conservation Engineering)
Analysis of erosivity indices with special reference to Kerala
Analysis of erosivity indices with special reference to Kerala